Technical and Economic Analysis of a 1 MWp Solar Power Plant in the Lake Toba Region: Potential and Impact on Green Tourism - Saut M Situmorang; Bonar S,M Naibaho (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2026)
This Lake Toba, one of Indonesiaâ€™s most prominent tourist destinations, holds significant potential to be developed into a sustainable and environmentally friendly tourism area through the integration of renewable energy. Among the available options, solar energy utilization via Solar Photovoltaic (PV) systems offers a strategic pathway to achieve energy sustainability and reduce reliance on fossil fuels. This study aims to evaluate the solar radiation potential, land requirements, technical design of Solar PV systems, and economic feasibility to support sustainable ecotourism development in the Lake Toba region. A quantitative research approach was applied, combining solar radiation assessment based on Global Horizontal Irradiance (GHI) data from BMKG and the Global Solar Atlas with financial feasibility analysis using Levelized Cost of Electricity (LCOE), Net Present Value (NPV), and Payback Period metrics. The results indicate that the Lake Toba region receives an average solar radiation of 4.8â€“5.1 kWh/mÂ²/day, allowing a 1 MWp Solar PV system to generate approximately 1.37 GWh of electricity annually. Economically, the system yields an estimated LCOE of USD 0.056/kWh, significantly lower than diesel-based generation costs of USD 0.15â€“0.20/kWh. Environmentally, such a system could reduce carbon emissions by around 1,163 tons of COâ‚‚ per year, directly supporting Indonesiaâ€™s national decarbonization argets. Overall, Solar PV deployment in the Lake Toba region is technically viable, economically competitive, and environmentally impactful, while also strengthening Lake Toba’s image as a green tourism destination.